2021
DOI: 10.1002/dad2.12195
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield volumes are associated with verbal memory after first‐ever ischemic stroke

Abstract: Introduction Hippocampal subfield volumes are more closely associated with cognitive impairment than whole hippocampal volume in many diseases. Both memory and whole hippocampal volume decline after stroke. Understanding the subfields’ temporal evolution could reveal valuable information about post‐stroke memory. Methods We sampled 120 participants (38 control, 82 stroke), with cognitive testing and 3T‐MRI available at 3 months and 3 years, from the Cognition and Neocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…( Pendlebury and Rothwell, 2019 ) Multiple cognitive functions may become impaired, though slower information processing and executive dysfunction tend to be predominant features of vascular cognitive impairment. ( Al-Qazzaz, 2014 , Cumming et al, 2013 ) Imaging markers including hippocampal atrophy ( Khlif, 2021 ) and brain parenchymal volume loss ( Bu, 2021 ) have been associated with cognitive/functional outcomes following ischaemic stroke. We reported lower total brain volume 3 years post-stroke in survivors who were cognitively impaired (CI) at 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…( Pendlebury and Rothwell, 2019 ) Multiple cognitive functions may become impaired, though slower information processing and executive dysfunction tend to be predominant features of vascular cognitive impairment. ( Al-Qazzaz, 2014 , Cumming et al, 2013 ) Imaging markers including hippocampal atrophy ( Khlif, 2021 ) and brain parenchymal volume loss ( Bu, 2021 ) have been associated with cognitive/functional outcomes following ischaemic stroke. We reported lower total brain volume 3 years post-stroke in survivors who were cognitively impaired (CI) at 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…Thalamic dysfunction has been implicated in the clinical impairments seen after stroke, with ipsi-and contralesional thalamic atrophy over the first year reported (12). In addition, we have previously reported that hippocampal subfield atrophy correlated better with verbal memory impairment in this cohort, suggesting that whole hippocampal atrophy may not be the metric of choice in post-stroke cognitive impairment (55). The observed reduction in TBV in stroke survivors and the strong association with greater TBV loss in those who were cognitively impaired at 3 months are novel.…”
Section: Discussionmentioning
confidence: 81%
“…Microstructural alterations in the ipsilateral hippocampus also occur after young onset stroke, 48 when concomitant degenerative changes are less likely to be a factor. Hippocampal subfield volumes correlate with verbal memory performance after stroke 49 and pathology studies reveal neuronal volume loss, which correlates with memory scores during life, consistent with secondary injury. 50 Given its role in cross-network integration, secondary changes in the thalamus could propagate across multiple networks and cognitive domains.…”
Section: Secondary Injury and Degenerationmentioning
confidence: 77%